Avaliação dos parâmetros químicos e potencial antioxidante do mel de jandaíra - Silva, Gerlania Sarmento da (2011)
The Jandaira bee( Meilipona subnitida D. ) it is a typical backcountry meliponineo and its considered endemic of northeastern Caatinga . Honey is appreciated by native populations, have a high commercial value and excellent quality (taste, smell, color, nutritional value, therapeutic, etc.), But is not well known in terms of chemical composition. This study aimed to determine the physicochemical characteristics (pH, free acidity, ash, protein, hydroxymethylfurfural , water activity and reducing sugars), thermal analysis ( differential scanning calorimetry with modulated temperature and thermogravimetry) and antioxidant activity (DPPH, ABTS, beta-carotene and linoleic acid and assay with 2-deoxyribose) of nine samples of pure Jandaira s honey collected in semi-arid region of Paraíba. The analysis of the total content, ultraviolet, infrared and melissopalinological analysis were also performed. With the data obtained in the ultraviolet spectrum the analysis of the major components were performed. The melissopalinological analysis showed the presence of 19 pollen types belonging to nine vegetables families and Mimosa caesalpinifolia was the predominant type in eight samples. It was observed that all samples showed a similar thermal behavior. Analysis of the infrared spectrum of honey in nature showed characteristic absorptions of sugars and phenolic compounds, the ultraviolet spectrum indicated the presence of conjugated substances that can be phenolic derivatives. Only sample 09 showed a different profile. The total phenolic content was around 1 % for pure honey. For antioxidant tests, the EC50 for antiradicalares assays diversify from 10.6 to 12.9 mg/mL and 6.1 to 9.7 mg / mL for DPPH and ABTS radical respectively. For the test with beta-carotene linoleic acid, time = 60 min (10 mg/ml), samples 1-8 presented inhibition between 48.8 and 58.4 % and the sample 09 inhibited 74.6%. For the inhibition of hydroxyl radical (2- deoxyribose), again the EC50 values were similar and varied from 2.1 to 2.3 mg/ml. From the data obtained it is possible to ensure a quality standard for Jandaira s honey associated with the use as a functional food, with beneficial properties to the body. This may lead an appreciation of the product by the consumer due of its traditional use as a sweetener that can provide a healthier alternative.